2023
DOI: 10.1002/pro.4728
|View full text |Cite
|
Sign up to set email alerts
|

An ankyrin repeat chaperone targets toxic oligomers during amyloidogenesis

Arpit Gupta,
Chuqi Lu,
Feng Wang
et al.

Abstract: Numerous age‐linked diseases are rooted in protein misfolding; this has motivated the development of small molecules and therapeutic antibodies that target the aggregation of disease‐linked proteins. Here we explore another approach: molecular chaperones with engineerable protein scaffolds such as the ankyrin repeat domain (ARD). We tested the ability of http://firstglance.jmol.org/fg.htm?mol=3DEO, a small, robust, ATP‐ and cofactor‐independent plant chaperone built from an ARD, to antagonize disease‐linked pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Fibrillation of Aβ42 was significantly slowed by cpSRP43 in a dose-dependent manner [65]. Transmission electron microscopy (TEM) imaging showed that Aβ40 and A syn fibrillation were significantly delayed in the presence of cpSRP43.…”
Section: Molecular Chaperone With Engineerable Protein Scaffoldsmentioning
confidence: 95%
See 4 more Smart Citations
“…Fibrillation of Aβ42 was significantly slowed by cpSRP43 in a dose-dependent manner [65]. Transmission electron microscopy (TEM) imaging showed that Aβ40 and A syn fibrillation were significantly delayed in the presence of cpSRP43.…”
Section: Molecular Chaperone With Engineerable Protein Scaffoldsmentioning
confidence: 95%
“…The 43 kD subunit of the chloroplast signal recognition particle (cpSRP43) is an ATP-independent plant chaperone shown to target Aβ oligomers [65]. It contains an engineerable protein scaffold ankyrin repeat domain (ARD).…”
Section: Molecular Chaperone With Engineerable Protein Scaffoldsmentioning
confidence: 99%
See 3 more Smart Citations